Pengembangan Panduan Pioneering pada Pramuka Penggalang Berbasis Project Berwawasan Profil Pelajar Pancasila - Mugiono, Teguh; Purnamasari, Iin; Ngatmini, Ngatmini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
Character education at SDN Simbangdesa 01 Batang Regency has not been going well, this is evidenced by the many cases of child delinquency that occur in the area, for example, children are less disciplined in flag ceremony activities, are less sporty in sports and arts activities, are less honest in their activities. academically, the child's sense of selfishness is still high, the lack of a culture of helping others. The non-optimal cultivation of character education within the scope of the academic community in Indonesia can result in a weak leader character which is associated with the increasing prevalence of corruption, chaos in the urban planning system, poor health services, loss of sense of justice, education that increasingly loses a compassionate conscience and is oriented towards noble character and other things. others that are not good for the mental development of students. The research is focused on integrated character development with Scouting extracurricular programs, pioneering activities for students at SDN Simbangdesa 01 especially grade 5 and grade 6 with project-based learning. The program at the school is designed to develop 18 character values that are focused on the character of responsibility, discipline, independence, and creativity in extracurricular activities of Pioneering Scouts. Extracurricular Scouting Pioneering can shape the character of students with the Pancasila profile. Project-based learning here is a forum that is deliberately prepared for students to carry out program projects that are assigned to them. Project-based learning expects students to be able to make decisions and create a framework in which problems whose solutions are not predetermined, design processes to achieve results, are responsible for obtaining and managing the information collected, carry out continuous evaluations, regularly review what they are doing. , the final result is a product and is evaluated for quality, and the class has an atmosphere that tolerates faults and changes.